Gdje u tijelu osjećamo stres? - rodne i dobne razlike - Jokić-Begić, Nataša (Array, 2009)
Objective: Although autonomous nervous system happens to be universally activated during stressful event, subjective experience of intensity and place where the change is present varies largely. The aim of the study was to identify gender and age differences in the perception of physiological changes during stressful event. Methods: Subjects were 564 children and 516 adults, males and females (age: 7 - 68 years). The drawing method was used which enabled denoting parts of the body without imposing preconceived ideas by the researcher. On the human body silhouette (outer outline of the human body, without parts of the face and hair, without fingers, without clothes and without gender characteristics) subjects had to denote parts of the body where they feel bodily changes during stressful situation. Results: Boys more frequently feel stress symptoms in the thorax and legs, and girls in head and abdominal organs. Younger children (up to 10 yrs) of both genders, in comparison to older children, more frequently feel stress symptoms in the neck, shoulders, arms and legs. Older subjects report more stress symptoms in internal organs, and women, in comparison to men, more frequently feel symptoms in the head, shoulders and chest. Adult men most frequently feel stress symptoms in gastrointestinal organs. Conclusion: It was found that there were age and gender differences in the perception of physiological changes during stressful situations and this has to be taken into account in the preventive and therapeutic interventions.